PENGARUH KUALITAS PRODUK, KEPERCAYAAN MEREK DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN LIPSTIK WARDAH DI KOTA SURABAYA - Sianturi, Angie Arni Giovani; Pudjoprastyono, Hery; Azhar, Ratih Mukti (Universitas Nusa Cendana, 2024)
In the era of rapid technological advancement, companies need to devise the right strategies and enhance innovation to attract consumers and excel in the dynamic market competition. This study aims to investigate the influence of product quality on purchasing decisions, examine the impact of brand trust on purchasing decisions, and explore the effect of social media marketing on purchasing decisions. The study employs a quantitative approach. The population consists of Wardah lipstick consumers in Surabaya City, and a sample of 120 respondents is drawn. Purposive sampling is utilized as the sampling technique. Data collection is conducted using questionnaires, and a Likert scale is employed to measure the variables in the study. The analysis technique used is partial least squares (PLS) analysis with the aid of SmartPLS software. The findings of the study reveal that product quality and brand trust significantly influence purchasing decisions. However, social media marketing does not significantly impact purchasing decisions. Keywords: Product Quality; Brand Trust; Social Media Marketing; Purchasing Decisions